The Influence of Compensation, Work Environment, and Transformational Leadership on Employee Work Productivity at Tirta Khayangan Regional Water Utility Company - Alvia Santoni; Deky Hamdani (The Future of Education Journal, 2026)
This study aims to examine the effect of compensation, work environment, and transformational leadership on employee work productivity at PDAM Tirta Khayangan, Sungai Penuh City. This research employed a quantitative approach with a causal associative design. The population consisted of all 30 employees of PDAM Tirta Khayangan, and a saturated sampling technique was applied. Data were collected using closed-ended questionnaires with a Likert scale and analyzed using multiple linear regression with SPSS. The results show that partially, the work environment has a positive and significant effect on employee work productivity, while compensation and transformational leadership do not have a significant effect. Simultaneously, compensation, work environment, and transformational leadership do not significantly affect employee work productivity. The coefficient of determination indicates that the independent variables explain 14.9% of the variation in employee productivity, while the remaining variation is influenced by other factors outside the research model.